Korelasi Kebugaran Kardiorespiratori dengan Partisipasi Siswa di Sekolah Dasar menggunakan Tes Foster - Rahmat Permana (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This study aims to analyze the relationship between the cardiorespiratory fitness of elementary school students, measured using the Foster Test, and their active participation in school activities. The research sample consisted of 75 students from three elementary schools in Tasikmalaya. Fitness data were categorized into four levels: Excellent (30 students), Good (18 students), Fair (15 students), and Poor (12 students). Active participation levels were measured using a questionnaire on participation in extracurricular school activities. The study employed a descriptive quantitative approach with Pearson correlation analysis to examine the relationship between variables. The results showed a significant positive correlation between cardiorespiratory fitness and students' active participation (r = 0.65, p < 0.01). Students in the Excellent and Good categories demonstrated higher levels of active participation compared to those in the Fair and Poor categories. Male students predominantly fell into the Excellent fitness category, while female students were more evenly distributed across lower categories. These findings underscore the importance of fitness programs in schools to enhance students' active participation, especially for those with lower fitness levels and female students. This study recommends the development of school-based fitness programs integrated into the curriculum to holistically support students' well-being and engagement.